Teaching in the right context: Textbook supply program, language, and vocabulary ability in Vietnam - FUJII, Tomoki (Institutional Knowledge at Singapore Management University, 2021)
While past two decades have witnessed a remarkable educational progress in Vietnam, ethnic minority children consistently lagged behind ethnic majority children in academic performance. The government of Vietnam has stepped up efforts to assist ethnic minority students in their learning by lowering the linguistic and cultural barriers they face. Among such efforts is the textbook supply program, and we examine its impact on the learning of children proxied by vocabulary test. We apply difference-in-differences estimation to four rounds of the Young Lives data between 2006 and 2015 in order to investigate how the textbook supply program narrowed the gap between the ethnic minority and majority over time. We show that the textbook supply program became more effective in narrowing the ethnic gap as the education policy in Vietnam became reoriented towards ethnic minority children. We also conduct a causal mediation analysis to explore the relevance of behavioural response through the change in time use. The result of this analysis suggests that increased study time is possibly a moderate mediator through which the textbook supply program helps narrow the ethnic gap in the test score only for the young cohort over and above the direct impact from the textbook program. This paper therefore alludes to the importance of delivering carefully designed materials for the target group to bring about meaningful behavioral changes. It also corroborates the findings from the recent literature on teaching at the right level.